Zonas de sentido sobre a governança corporativa - Alexandre Santos Pinheiro (2010)
The proposal of this work is to provide an ideological and/or philosophical dimension (POPPER) about the phenomenon of corporate governance. The teleological function of this research is the construction of processes of intelligibility (Zones of Sense) about corporategovernance. We have chosed an epistemological process based on two pillars: (1) on the "Qualitative Epistemology" (REY, 2005) as search process and (2) above viewpoint of subject, its process according to the Historic-Cultural of Subjectivity. Our empirical data base consisted of non-structured interviews with 20 study subjects (divided into four categories: academics, boards, CEOs and consultants), which was analyzed by the Content Analysis (BARDIN, 2004). Theoretical aspects were explored during the whole research, coming out, from that, counterpoints and contradictions about the subjects relations and the conceptual development of the issue. The "Traditional Approach to Corporate Governance" was noticed as an immanent process of the rupture between the ownerships and managers according toBobbio's taxonomy (1987), economic power and ideological power prevailing a Manichean meaning of the second group of actors. In the Traditional Approach on Corporate Governance, we have observed an institutionalization process of the directors behavior (directors of organizations where there is the division between property and control) that relies on some kind of functional-instrumental rationality, so it may determine how a corporation should be governed. Nevertheless, we believe that an attempt to explain corporate governance should exclude normative issues in the same way, they should not focus oninstitutional designs or on conflict resolutions mechanisms. Even though the governance´s phenomenon is a result from the dissociation of ownership and management, to debate only the relationship between actors do not address the aspects and nature that the meaning ofcorporate governance should consider. In other words, governance should be understood under a substantive rationality. Therefore, power, consensus and hegemony form the triad of elements that support the proposition of a zone of sense. These elements are complementedby the degree of intensity that the significant groups (agents with claims) organize and manifested themselves around the corporation. In this work, corporate governance is discussed as a social political process that seeks to build a consensus among the relevant publics of the company, thus the result of this process is the company legitimacy before eachone of the significant stakeholder groups". Studying the government of a corporation should cover the power relations in the organization. The governance ponders, at this hermeneutic, that social agents build shared goals using the organizational strategies. Shared goals mean, asfar as possible, to satisfy the particular purposes of each stakeholder (MOORE, 1999). Governing a corporation means the mediation of symbolic elements, not presented to the different organized groups of the society, but that become significant as soon as a discursive resource (or language) is used, expressing some kind of rationalization through them.